Chronic Occupational Exposure to Chemical Mixtures Induces Genomic Instability in Paint Workers - Iritas, Servet Birgin; Bacanli, Merve Gudul; Taner, Gokce; Turksoy, Vugar Ali; Tutkun, Lutfiye; Yilmaz, Omer Hinc; Basaran, Ayse Nursen (Mdpi, 2025)
This study's objective was to evaluate genotoxic effects on automotive paint workers who are exposed to a complex mixture of VOCs, heavy metals, and solvents. Biological samples, including blood, urine, and buccal epithelial cells, were collected from 80 exposed workers and 80 demographically matched control subjects. DNA damage was assessed using the alkaline COMET assay in lymphocytes and whole blood. The Buccal Micronucleus Cytome (BMCyt) assay was also employed to identify cytogenetic abnormalities. Additionally, trichloroacetic acid (TCA), hippuric acid (HA), phenol, and lead (Pb) levels were measured as biomarkers of exposure. A significant increase in DNA damage was observed in the lymphocytes and whole blood of exposed workers (p < 0.05) BMCyt analysis also revealed higher frequencies of micronuclei (MN), binucleated cells, condensed chromatin (CC), and karyorrhectic (KHC) and pyknotic cells (PYC) in buccal cells (p < 0.05). Elevated levels of urinary HA, phenol, TCA, and blood lead indicated systemic chemical exposure. DNA damage positively correlated with these biomarkers, supporting a strong link between chronic occupational exposure and genotoxicity. The findings from this study highlight the critical importance of implementing effective safety measures and consistent biomonitoring for paint workers to prevent adverse health effects.
Keywords: paint workers; occupational exposure; DNA damage; comet assay; buccal micronucleus assay; trichloroacetic acid; hippuric acid; phenol; lead